A qualidade de vida na habitação social verticalizada a partir da avaliação pós-ocupação: o caso do conjunto habitacional cidade verde - Araújo, Débora Cristina (2016)
The post-occupancy evaluation (POE) of social enterprises has been widely discussed in Brazil, these research related to the evaluation of the quality of the project, materials and behavior in space, among other issues. However, also evaluate whether POE a lack of research to consider quality of life as an evaluation method of housing. In this sense, starting from the hypothesis that the vertical housing developments do not provide quality of life to its residents, this research aimed to develop an POE methodology of quality of life of residents of social vertical housing taking up based on three levels of evaluation of quality of life: the HDI - Human Development Index, the Social Progress Index - SPI and the Welfare Index Urban – WIU. As a pilot, evaluated the housing Cidade Verde, located in Uberlandia, Minas Gerais. Methodologically, the research is divided into: i) approach to the object, the vertical social housing; ii) the user about the approach and the main factors that can influence their quality of life, considering the HDI indicators, SPI and WIU; iii) definition of APO and description of the methods used in the research; and iv) a description of the case study, the results of the walkthrough, questionnaires and focus group, findings and recommendations of cards. The results of the POE indicated poor quality of life in the assessed enterprise and dissatisfactions related to low architectural and construction quality, as the small spaces and compartmentalisation of units, the lack of public facilities in the surroundings, lack of privacy, among other issues. There was also that the project is presented as a repeater model of the old Brazilian housing proposals and do not show progress in relation to meet the contemporary demands of the residents. Furthermore, this research points out recommendations for future social housing developments upright so that it can provide higher quality of life for its residents.